2003
DOI: 10.1002/jmv.10447
|View full text |Cite
|
Sign up to set email alerts
|

Differential patterns of human cytomegalovirus gene expression in various T‐cell lines carrying human T‐cell leukemia‐lymphoma virus type I: Role of tax‐activated cellular transcription factors

Abstract: Replication of human cytomegalovirus (HCMV) was investigated in various T-cell lines expressing the tax gene product of human T-cell leukemia-lymphoma virus type I (HTLV-I). Differential patterns of HCMV replication were found in HTLV-I-carrying cell lines. HCMV gene expression was restricted to the immediate-early genes in MT-2 and MT-4 cells, whereas full replication cycle of the virus was observed in C8166-45 cells. Productive HCMV infection induced a cytopathic effect resulting in the lysis of infected cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2006
2006
2007
2007

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
1
1
Order By: Relevance
“…Cell-typedependent effects of Tax on cellular transcription factors have been known for years. While Tax had a positive effect on NF-B activity but no effect or a slightly negative effect on Sp1 activity in HL-60 cells in this study, Sp1 activity was reported to be variable among HTLV-1 Tax-positive cell lines (3).…”
Section: Discussioncontrasting
confidence: 61%
“…Cell-typedependent effects of Tax on cellular transcription factors have been known for years. While Tax had a positive effect on NF-B activity but no effect or a slightly negative effect on Sp1 activity in HL-60 cells in this study, Sp1 activity was reported to be variable among HTLV-1 Tax-positive cell lines (3).…”
Section: Discussioncontrasting
confidence: 61%
“…Huh-7 cells were incubated with 20 μg/ml of DHMEQ for 1-24 h. The nuclear extract was prepared as described previously (22). As a positive control, the nuclear extract from HUT-78 cells containing NF-κB (23) . Immunofluorescence for rhodamine was analyzed by Olympus BX50 microscope (Tokyo, Japan) and images were digitally captured using a Nikon DXM 1200 digital camera (Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%